2015
DOI: 10.1053/j.jrn.2014.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Physical Activity and Sitting Time Among Patients on Hemodialysis Using a New Physical Activity Instrument

Abstract: Objective Physical activity questionnaires usually focus on moderate to vigorous activities and may not accurately capture physical activity or variation in levels of activity among extremely inactive groups like dialysis patients. Design Cross-sectional study Setting Three dialysis facilities in the San Francisco Bay Area Subjects 68 prevalent hemodialysis patients Intervention We administered a new physical activity questionnaire designed to capture activity in the lower end of the range, the Low Phy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
38
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(43 citation statements)
references
References 19 publications
4
38
1
Order By: Relevance
“…The initial search yielded 431 citations. Of these 27 [ 5 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 ] studies met inclusion criteria ( Figure 1 ). Characteristics of the studies included are presented in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The initial search yielded 431 citations. Of these 27 [ 5 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 ] studies met inclusion criteria ( Figure 1 ). Characteristics of the studies included are presented in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Characteristics of the studies included are presented in Table 1 . Sixteen [ 5 , 22 , 23 , 25 , 27 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 39 , 40 , 42 , 45 ] of the 27 studies published a single point data, four studies [ 28 , 29 , 30 , 34 ] utilized pre-post design to evaluate the effect of exercises and seven studies [ 24 , 26 , 38 , 41 , 44 , 46 , 47 ] used a controlled trial design to evaluate effect of either nutritional or exercise intervention in this population. The baseline values of the participants in these studies were utilized for analysis evaluating the effect of HD on spatio-temporal gait parameters.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A Low Physical Activity Questionnaire has been developed to assess and can additionally be used for monitoring physical activity. 8 Although it was developed for patients on hemodialysis, this instrument would also be pertinent for use with the CKD patient population. After identifying areas to improve on, the RDN may recommend structured activities including aerobic, strength, and flexibility exercises.…”
mentioning
confidence: 99%
“…The present study showed that many elderly patients undergoing HD had moderate to severe difficulty in ADL tasks compared with communitydwelling elderly adults. Patients undergoing HD have multiple comorbidities [1,3], an inactive lifestyle [32], and physical frailty [4,5], and these factors form a vicious circle. Therefore, we consider that the deterioration of kidney function leading to HD and the initiation of HD adversely affected ADL difficulty similar to ADL dependency.…”
Section: Discussionmentioning
confidence: 99%